SP-C1 tongue squamous cell carcinoma, ethanol fraction of ant nest plant, proliferation - Harun Achmad; Supriatno Supriatno; Marhamah Marhamah; Rasmidar Rasmidar (DiscoverSys Inc., 2014)
Squamous cell carcinoma at the tongue is a malignant tumor derived from epithelial mucosa of the oral cavity. Thisstudy aims to identify and to analyze the effect of flavonoid fraction of etanol of ant nests plants (Myrmecodia pendans)as an anti-cancer barrier against the proliferation of SP-C1 tongue cancer cells. The study was conducted with pureexperimental laboratory methods using Supri's-Clone 1 (SP-C1) human tongue cancer cells cultured. Researchgradually begins with determination, extraction and fractionation ant nests plant, cytotoxicity test to get a fraction offlavonoids that have anticancer potential,and finaly testing the proliferation barriers. Cytotoxicity test showed thatfrom the highest concentration (1000 Î¼g/mL) to the lowest concentration (7.8125 Î¼g/mL) in etanol fraction, fractionhexan and water caused Sp-C1 human tongue cancer cells death significantly. Ethanol fraction LCvalues of 938,003.These results were obtained from the linear equivalent of the relation between log consentration and probit. Flavonoidetanol fraction of ant nest has an inhibition effect against proliferation of SP-C1. Antiproliferative analysis of flavonoidfraction of ethanol flavonoid based on concentration and incubation time on optical density absorbation SP-C1 cellswas statistically highly significant (p=0.00).